2016
DOI: 10.1039/c5gc02268a
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis reaction networks for lignin model compounds: unraveling thermal deconstruction of β-O-4 and α-O-4 compounds

Abstract: Although lignin is one of the main components of biomass, its pyrolysis chemistry is not well understood due to complex heterogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
88
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 51 publications
5
88
0
Order By: Relevance
“…With a cleavage of α‐O‐4 bond a radical with aromatic core is formed that is resonantly stabilized, in contrast to the β‐O‐4 bond cleavage of the trimer molecule. Therefore, the molecules with β‐O‐4 decompose predominantly via concerted mechanisms (Choi et al, ).…”
Section: Mechanistic and Intrinsic Kinetic Studies Of Biomass Pyrolysismentioning
confidence: 99%
See 2 more Smart Citations
“…With a cleavage of α‐O‐4 bond a radical with aromatic core is formed that is resonantly stabilized, in contrast to the β‐O‐4 bond cleavage of the trimer molecule. Therefore, the molecules with β‐O‐4 decompose predominantly via concerted mechanisms (Choi et al, ).…”
Section: Mechanistic and Intrinsic Kinetic Studies Of Biomass Pyrolysismentioning
confidence: 99%
“…Besides, these studies can also help in designing a suitable catalyst to improve the selectivity towards desired products (Butler et al, ; Li et al, ). Numerous studies have been performed over the years to decode the kinetic mechanisms of biomass fast pyrolysis (Agarwal, Dauenhauer, Huber, & Auerbach, ; Bai et al, ; Bai & Brown, ; Banyasz, Li, Lyons‐Hart, & Shafer, ; Bradbury, Sakai, & Shafizadeh, ; Branca, Di Blasi, Mango, & Hrablay, ; Broido & Nelson, ; Choi et al, ; Chu, Subrahmanyam, & Huber, ; Custodis, Hemberger, Ma, & van Bokhoven, ; Debiagi et al, ; Faravelli, Frassoldati, Migliavacca, & Ranzi, ; Gai et al, ; Huang, Liu, Tong, Li, & Wu, ; Huang, Liu, Wei, Huang, & Li, ; Kawamoto, Murayama, & Saka, ; Kawamoto & Saka, ; Khachatryan, Xu, Wu, Pechagin, & Asatryan, ; Kim, Bai, & Brown, ; Lou, Wu, & Lyu, ; Mayes & Broadbelt, ; Mayes, Nolte, Beckham, Shanks, & Broadbelt, ; Mettler, Mushrif, et al, 2012; Miller & Bellan, ; Norinaga, Shoji, Kudo, & Hayashi, ; Nowakowska, Herbinet, Dufour, & Glaude, ; Patwardhan, Dalluge, Shanks, & Brown, ; Patwardhan, Satrio, Brown, & Shanks, ; Piskorz, Majerski, Radlein, Vladars‐Usas, & Scott, ; Piskorz, Radlein, & Scott, ; Ranzi et al, , ; Ranzi, Debiagi, & Frassoldati, , ; Ronsse, Dalluge, Prins, & Brown, ; Scheer et al, ; Scheer, Mukarakate, Robichaud, Nimlos, & Ellison, ; Shafizadeh & Fu, ; Shen & Gu, ; Shen, Gu, & Bridgwater, ; Shen, Xiao, Gu, & Luo, ; Varhegyi, Jakab, & Antal, ; Vasiliou et al, ; Vinu & Broadbelt, ; Wang, Ru, Lin, & Luo, ; Werner, Pommer, & Broström, ; Zhang, Li, Yang, & Blasiak, ; Zhang, Nolte, & Shanks, ; Zhou, Li, Mabon, & Broadbelt, ; Zhou, Nolte, Mayes, Shanks, & Broadbelt,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Lignin constitutes 25-35 %o ft he organic matrix of lignocellulosic biomass, adding strength and rigidity to cell walls. [10] The hydrothermal conversion of benzylp henyle ther,asimple model compound reminiscent of a-O-4 linkages, has been studied by Siskin et al [11] and Lercher and co-workers. Of these,t he b-O-4 linkage predominates, accounting foro ver5 0% of the cross-links.…”
mentioning
confidence: 99%
“…[8] The chemistry of lignin under hydrothermalc onditions is comparatively less well understood [2,9] than that under pyrolysis conditions when linkages such as b-O-4 and a-O-4 are broken down through free radicalc hemistrya nd react further in pericyclic reactions. [10] The hydrothermal conversion of benzylp henyle ther,asimple model compound reminiscent of a-O-4 linkages, has been studied by Siskin et al [11] and Lercher and co-workers. [12] They demonstrated that the ether hydrolyzed to benzyl alcohol and phenol.…”
mentioning
confidence: 99%